A Conforming Triangular Plane Element with Rotational Degrees of Freedom. (20th May 2015) - Fu, Xiang-Rong; Yuan, Ming-Wu; Pu, Chen
Abstract : This paper presents a novel way to formulate the triangular plane element with rotational degrees of freedom (RDOF). The linear distribution of rotational displacement is assumed. The conforming displacement along the sides based on the rotational displacement assumption is derived, and the triangular plane element TR3 for isotropic material is formulated. By using the explicit integral formulae of the triangular element, the matrices used in the proposed plane element TR3 are calculated efficiently. The benchmark examples showed thier high accuracy and high efficiency.